Karakter Kreatifitas Dan Kemandirian Pada Siswa(Studi Kasus Pada Proses Pembelajaran Mata Pelajaran Prakarya dan Kewirausahaan Pada Siswa Kelas XI Di SMA Negeri 8 Surakarta) - Adhinurrofiq, Asna; , Dra, Hj. Sri Gunarsih, SH., MH (2016)
This study aimed to describe the character of creativity and independence in students through the learning process craft and entrepreneurial subjects in SMAN 8 of Surakarta in academic year 2014/201. The study used a qualitative approach, data collection through interviews, observation, and documentation. Test the validity of the data by triangulation of sources and techniques or methods of data collection. Applying the model of interactive data analysis through data collection, data reduction, data presentation, and conclusion. These results indicate that the educational character of creativity and independence are always provided by the SMA 8 Surakarta to learners through the learning process craft and entrepreneurial subjects. This is always done for programs that have been compiled has become a priority in the school SMAN 8 of Surakarta can instill creativity and independence of character education to students. Obstacles encountered by SMA 8 Surakarta in applying the character of creativity and independence in students through the learning process, the first coming from the part of some teachers as teachers of subjects craft and independence to the character of the material that is sometimes limited, causing the character of creativity and independence less walk maximum, besides the second obstacle comes from the majority of learners were still unruly. Solutions to overcome obstacles in the character of creativity and independence in students through learning the craft and entrepreneurial school in SMAN 8 Surakarta, namely to establish a good relationship from the school SMA N 8 of Surakarta with all components relating namely education department of youth and sports, as well as regular participation the results of students in craft fairs both at the city or provincial level.